A New Energy-Efficient Building System Based on Insulated Concrete Perforated Brick with a Sandwich - Xing, Guoqi; Yu, Jing-jie; Zhang, Chun-gang; Wu, Jun-xi (Civil Engineering Journal, 2018)
The purpose of this research is to put forward a new energy-efficient building system that can meet the energy saving requirement of 65% for public buildings in cold areas based on modified insulated concrete perforated brick with a sandwich. Modified brick was composed of three parts and three parts can be made a whole in brick manufacturing and it was called self-thermal insulation concrete perforated brick and could avoid appearance of cracks. The tesst was done to obtain thickness of EPS for modified insulated concrete perforated brick with a sandwich in order to meet the requirement of insulation. Thickness of EPS was set to to 45, 50, 55, 60, 65 and 75 mm respectively and comparative experiments were also carried out to verify the effect of insulation for modified bricks and unmodified bricks. Field tests were carried out to obtain appropriate masonry methods for modified bricks. Based on the results of analysis and discussion, then obtained: (1) Heat transfer coefficient of wall made by modified bricks was less than heat transfer coefficient of wall made by unmodified bricks when the same for thickness of EPS, it could be reduce by up to 45%; (2) When thickness of insulating layer was 65 mm, heat transfer coefficient of wall made by modified bricks could reached minimum limit 0.45 and it could meet energy saving requirement of 65% for buildings in cold area. (3) Insulating layer, located inside of the wall, could avoid appearance of cracks on surface of wall for modified bricks.